Integrasi Aspek Lingkungan dalam Pemilihan Pemasok: Strategi untuk Keberlanjutan Rantai Pasokan - Wahyu Elanda, Redian; Simbolon, Oky; Laymina Ikhsan, Wakhid (Jurnal Serambi Engineering, 2025)
This research aims to design supplier performance criteria using an environmentally-oriented approach within the context of supply chain management. Amid increasing awareness of environmental issues, companies need to consider the environmental impact when selecting and evaluating suppliers. Through a literature review, this study identifies relevant performance factors and systematically designs evaluation criteria with input from experts. This approach employs multi-criteria analysis to assess environmental aspects of supplier performance, including energy efficiency, emission reduction, waste management, and the use of eco-friendly raw materials. The results indicate that implementing environmentally-oriented criteria can enhance a company's effectiveness in selecting environmentally responsible suppliers. By integrating environmental factors into supplier evaluations, companies can not only mitigate negative environmental impacts but also contribute to sustainable development. These findings provide important guidance for companies in designing evaluation criteria that consider environmental aspects, as well as enhancing the understanding of the significance of sustainable supply chain management. This research is expected to fill gaps in the related literature and promote more responsible business practices.